Hygiene Behavior And The Risk Of Hepatitis Among Street Food Vendors In Surabaya - Alfia, Nur Laili; Setyawan, Yuswanto (Poltekkes Kemenkes Kupang, 2025)
Background: Street food vendors are a vital part of urban food systems in Indonesia, yet their hygiene practices remain poorly regulated, contributing to the spread of foodborne diseases such as hepatitis. Objective: This study aimed to analyze the relationship between hygiene behavior and the risk of hepatitis among street food vendors in Surabaya. Method: A quantitative analytical method with a cross-sectional design was applied to 120 purposively selected vendors. Data were collected through structured questionnaires assessing hygiene practices and self-reported hepatitis symptoms. Results: Chi-Square and Spearman correlation tests revealed significant associations between handwashing (p = 0.002), glove use (p = 0.011), access to clean water (p = 0.001), and food covering (p = 0.005) with hepatitis risk. The strongest negative correlation was found between clean water access and hepatitis symptoms (ρ = –0.48). These results highlight the critical role of basic hygiene practices in preventing hepatitis transmission in informal food settings. Findings suggest that targeted health education and improved water access can reduce public health risks. This study supports the integration of food safety standards into street food regulation and community-based interventions. Strengthening hygiene behavior among vendors could significantly reduce the burden of hepatitis in high-density urban environments.